Human capital accumulation and economic growth in Malaysia – investigating the long run Nexus - Lai, Wei Sieng; Ishak Yussof (Penerbit Universiti Kebangsaan Malaysia, 2014)
The endogenous growth theory emphasises that human capital is crucial to a country’s economic growth. The purpose of the present study is to investigate the long term relationship between human capital and economic growth in Malaysia for the period between 1981 and 2010. Based upon the results of the autoregressive distributed lag (ARDL) model employed, the findings indicate that a long run relationship exists between the education level of the labour force and economic growth. Among all education levels, labour with high educational attainment (secondary and tertiary) contributed positively to economic growth. The present study recommends further investment in higher education following the successful experience of many developed countries in order to propel Malaysia towards achieving its ambition of being recognised as a high income country.